Job polarisation and the middle class New evidence on the changing relationship between skill levels and household income levels from 18 OECD countries - Salvatori, Andrea (OECD Social, Employment and Migration Working Papers, 2019)
Labour markets across the OECD have polarised in recent decades, as the share of middle skill occupations has declined relative to that of both high- and low skill occupations. This paper shows that, contrary to what is often assumed in the public debate, job polarisation has not resulted in a decline in the share of households with middle-income across 18 OECD countries. Most of the changes in the share of middle-income households result instead from changes in the propensity of workers in different occupations to be in it. In fact the results point to a change in the relationship between occupational skill levels and household income as both middle and high skill jobs increasingly fail to deliver on the promise of the relative income status traditionally associated with their skill level. These changes might help explain some of the social frustration that has been at the centre of the political debate in recent years